Techniques for evaluation of medicinal plant products as antimicrobial agent: Current methods and future trends - Das, K.; Tiwari, R. K. S.; Shrivastava, D.K. (2010)
Pharmaceutical and scientific communities have recently received the attention of the medicinal plants and various publications have documented the therapeutic worth of natural compounds to validate the claims of their biological activity. Profuse use of commercial antibiotic and synthetic pesticides for human and crop protection is harmful to human health, ecosystem and environment. Attention has also been drawn to the antimicrobial properties of plants and their metabolites due to the growing incidences of drug-resistant pathogens of both clinical and agricultural importance. Medicinal plants have their intrinsic ability to resist pathogenic microorganisms and this has led the researchers to investigate their mechanisms of action and isolation of active compounds. This has enabled exploitation of medicinal plants for the treatment of microbial infections of both plants and humans by developing new antimicrobial agents. This novel search entails extensive research and it is therefore imperative to follow standard methods to authenticate claims of antimicrobial action. This paper reviewed the methods being employed earlier and recently in use related to investigations of the antimicrobial efficacy of medicinal plant extracts. Standard protocols of the various techniques used by different authors are also mentioned. Key words: Medicinal plants, plant extracts, antimicrobial activity, phytochemicals.